Heat shock protein complex vaccines induce antibodies against Neisseria meningitidis via a MyD88-independent mechanism. Issue 14 (29th March 2016) - Han, Jia Xi; Ng, Garrett Z.; Cecchini, Paola; Chionh, Yok Teng; Saeed, Muhammad A.; Næss, Lisbeth M.; Joachim, Michael; Blandford, Lucy E.; Strugnell, Richard A.; Colaco, Camilo A.; Sutton, Philip
Abstract: Background: Neisseria meningitidis are common colonizers of the human nasopharynx. In some circumstances, N. meningitidis becomes an opportunistic pathogen that invades tissues and causes meningitis. While a vaccine against a number of serogroups has been in effective use for many years, a vaccine against N. meningitidis group B has not yet been universally adopted. Bacterial heat shock protein complex (HSPC) vaccines comprise bacterial HSPs, purified with their chaperoned protein cargo. HSPC vaccines use the intrinsic adjuvant activity of their HSP, thought to act via Toll-like receptors (TLR), to induce an immune response against their cargo antigens. This study evaluated HSPC vaccines from N. meningitidis and the closely related commensal N. lactamica . Results: The protein composition of N. lactamica and N. meningitidis HSPCs were similar. Using human HEK293 cells we found that both HSPCs can induce an innate immune response via activation of TLR2. However, stimulation of TLR2 or TLR4 deficient murine splenocytes revealed that HSPCs can activate an innate immune response via multiple receptors. Vaccination of wildtype mice with the Neisseria HSPC induced a strong antibody response and a Th1-restricted T helper response. However, vaccination of mice deficient in the major TLR adaptor protein, MyD88, revealed that while the Th1 response to Neisseria HSPC requires MyD88, these vaccines unexpectedly induced an antigen-specific antibody response via a MyD88-independent mechanism. Conclusions: N. lactamica and N. meningitidis HSPC vaccines both have potential utility for immunising against neisserial meningitis without the requirement for an exogenous adjuvant. The mode of action of these vaccines is highly complex, with HSPCs inducing immune responses via both MyD88-dependent and -independent mechanisms. In particular, these HSPC vaccines induced an antibody response without detectable T cell help.